Dependence of Moral Culture of Senior Pupils on Type of School - Girdzijauskas, Arvydas (Acta Paedagogica Vilnensia, 2007)
Problems of education are very closely bonded with problems of culture. Cognition is connected with other people individual meet - compete or cooperate - in social surrounding, so it has moral dimension. At the same time it is connected with culture, as social life is a kind of cultural life. If individuals moral representation is found not isolated, but in the context of particular culture, the moral culture of personality can be discussed. Moral culture of personality is related to its artistic, in particular musical activity. Pieces of art, as other cultural models - religious, philosophical, scientific, ideological – can be understood as programs, presenting project of organization of social and psychological processes, like genetic systems present model of structure of organic processes. This article presents concept of moral culture of senior pupils as well as seeks to reveal dependence of its practical component expression (stability, creativity and authenticity of behaviour and its motives) on character of musical activity in different type of schools. The investigation of moral culture was based on ideas of cognitive anthropology, existential and hermeneutic philosophy. Stability of behaviour and strong intrinsic motivation of members of choral singing schools possibly related to high quality of performance achieved by these groups and emotions of success and aesthetic suggestibility. Also assumption is possible that free and independent self-determination to take part in musical activity typical to members of groups of informal music education, can influence their motivation and stability of behaviour.